Zambia is the place to bee - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Honey be, oh honey bee. The Biblical Samson ate it to keep up his strength. It was bartered for silk along the Asian trade routes through Samarkand seven centuries ago. Ancient Greeks and Romans made love potions of it. Honey and other products of...